Guo Zhongshu's Archaeology of Writing. Issue 2 (July 2019) - Hay, Jonathan
Abstract : "Bird-tracks" and "tadpoles" are both names for ancient script. As customs changed, the script came to be used less and less, until any basis for knowledgeable discussion was lost and it was known only from hearsay. The Grand Preceptor said: "When the [ forms of the ] rites are lost, search for them in the countryside." Might not ancient script be even better than the countryside? The names of dozens of artists from the tenth century have come down to us, for the most part with very little information about their lives and scarcely more about their art. Fortunately, the life and professional career of Guo Zhongshu 郭忠恕 (928–977) can be reconstructed in enough detail to give a sense of the personality of the artist and the world that he experienced. Indeed, we are doubly fortunate because Guo, it turns out, had no ordinary life. Known to art historians today primarily as one of the great painters of architectural subjects in Chinese history, Guo entered adult life in a different guise, as a brilliant young paleographer and calligrapher. This aspect of his career, no less important than his painting, is the subject of the present study. Although specialists have recognized his scholarly and calligraphic achievements, we still lack a contextualized account that incorporates what can be known of his biography and social circumstances. More important for the theme of this special issue, the material dimension of Guo's paleographic and calligraphic activities also remains to be explored. Any discussion can only be very partial, however, since no manuscripts or autograph calligraphies survive, only stone steles; fortunately, Guo's engagement with stele production is in itself of the highest historical interest. The chronologically organized text that follows tells a biographical story, with as much detail as the available sources allow, which eventually opens out onto the material world of steles, before returning to biography to recount the last chapter of Guo Zongshu's life. Rather than offering a conclusion, I end with a reflection on the materialities of transmission of paleographic and calligraphic knowledge. For the purposes of this article I have not thought it necessary to choose between the very different lenses of biography and material culture, since my goal is not to prove a thesis but to reconstruct an unfamiliar world. As I hope to show, the understanding of one person's life can enrich the understanding of artifacts associated directly and indirectly with the person, and vice versa.